Flowering and Seed Development Characteristic of Citrus Derived from Somatic Hybridization of Mandarin Satsuma (Citrus unshiu Marc.) and Siam Madu (Citrus nobilis Lour.) - Imroatus Saâ€™adah; Eny Widajati; Mia Kosmiatin; Endah Retno Palupi (AGRIVITA, Journal of Agricultural Science, 2022)
The somatic hybridization between Mandarin Satsuma (Citrus unshiu Marc.) and Siam Madu (Citrus nobilis Lour.) is expected to produce progenies having sweet seedless fruit. The research was aimed to study flowering biology, fruit and seed development to identify parthenocarpic lines derived from somatic hybridization. The research was carried out at Pacet Experimental Station of ICABIOGRAD, Cianjur, West Java (1150 m asl), during August 2019-July 2020. The research materials were 15 citrus lines derived from somatic hybridization between Mandarin Satsuma and Siam Madu, of which 5 plants (Â± 2 years old) per line were prepared. Observation was carried out on flowering phenology, flower morphology, fruit development, pollen viability, and stigma receptivity. Seedless fruits from un-pollinated, selfpollinated, and cross-pollinated flowers of each line were investigated. The results showed that flower morphology of the 15 citrus lines varied in the number of petals, flower diameter, pistil length relative to the stamen, and number of stamen. The development from bud emergence to fruit ripening also varied among and within lines, ranging from 212 to 316 days. Among the lines, FS 25 showed a stronger character towards stimulative parthenocarpy. FS 84 and FS 89 were potential sources of pollen (pollenizer) to produce seedless fruits.